2017
DOI: 10.3847/1538-4357/aa9069
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Presence of Glycolaldehyde and Ethylene Glycol around Sagittarius B2

Abstract: We report the detection of widespread CH 2 OHCHO and HOCH 2 CH 2 OH emission in Galactic center giant molecular cloud Sagittarius B2 using the Shanghai Tianma 65m Radio Telescope. Our observations show for the first time that the spatial distribution of these two important prebiotic molecules extends over 15 arc-minutes, corresponding to a linear size of approximately 36 pc. These two molecules are not just distributed in or near the hot cores. The abundance of these two molecules seems to decrease from the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
4
29
0
Order By: Relevance
“…They suggested that CH 2 (OH)CHO was much more extended compared to CH 3 OCHO and its emission was spatially filtered by the interferometric character of the observations. These findings are supported by the more recent study of Li et al (2017) towards an extended region of the Galactic Centre in which the authors reported cold gas emission of CH 2 (OH)CHO ∼36 pc in width around Sgr B2(N). We note that, these two observations of the CH 2 (OH)CHO spatial extent are specific to the Galactic Centre, where non-thermal desorption processes put the CH 2 (OH)CHO in the gas phase at temperatures much lower than the thermal desorption temperature of this species.…”
Section: Spatial Extentsupporting
confidence: 78%
“…They suggested that CH 2 (OH)CHO was much more extended compared to CH 3 OCHO and its emission was spatially filtered by the interferometric character of the observations. These findings are supported by the more recent study of Li et al (2017) towards an extended region of the Galactic Centre in which the authors reported cold gas emission of CH 2 (OH)CHO ∼36 pc in width around Sgr B2(N). We note that, these two observations of the CH 2 (OH)CHO spatial extent are specific to the Galactic Centre, where non-thermal desorption processes put the CH 2 (OH)CHO in the gas phase at temperatures much lower than the thermal desorption temperature of this species.…”
Section: Spatial Extentsupporting
confidence: 78%
“…Most of these reactions have been studied experimentally in various ways (Fedoseev et al 2015;Butscher et al 2015;Chuang et al 2016;Fedoseev et al 2017;Chuang et al 2017;Butscher et al 2017) and they have also been proposed by and are included in a number of astrochemical model studies (Garrod et al 2008;Woods et al 2012;Coutens et al 2018). Similar conclusions are also supported by observational work for specific species (Rivilla et al 2017;Li et al 2017). Despite this significant amount of investigations, relatively little is known about the reaction rate constants at low temperature, while these are the crucial parameters needed to constrain modeling studies.…”
Section: Introductionsupporting
confidence: 65%
“…The 89 GHz transitions with a higher upper-level energy (26.43 K) are regarded as coming from the 'warm' phase, while transitions with a lower upper-level energy (1.2 K) are regarded as coming from the 'cold' phase. The 'cold' glycolaldehyde was found to be widespread around the Sgr B2 complex (Li et al 2017). Fig.…”
Section: Speciesmentioning
confidence: 99%
“…Many COMs are first detected toward Sgr B2(N), such as glycoaldehyde CH 2 OHCHO (Hollis, Lovas & Jewell 2000), ethylene glycol HOCH 2 CH 2 OH (Hollis, Lovas & Jewell 2002), amino acetonitrile H 2 NCH 2 CN (Belloche et al 2008) and so on. Some COMs, such as glycolaldehyde and ethylene glycol, were found to be widespread in the Galactic centre (Hollis et al 2001;Requena-Torres et al 2006, 2008Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%